2002
DOI: 10.1007/s0033501-2109-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, physical, and comparative map of the subtelomeric region of mouse Chromosome 4

Abstract: The subtelomeric region of mouse chromosome (Chr) 4 harbors loci with effects on behavior, development, and disease susceptibility. Regions near the telomeres are more difficult to map and characterize than other areas because of the unique features of subtelomeric DNA. As a result of these problems, the available mapping information for this part of mouse Chr 4 was insufficient to pursue candidate gene evaluation. Therefore, we sought to characterize the area in greater detail by creating a comprehensive gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Further, in Drosophila, the behavioral and electrophysiological responses to trehalose are diminished in two mutants that carry deletions in the trehalose recognition gene, Gr5a [27]. In the mouse, variation in preference for sweet-tasting stimuli maps to the gene for T1R3, located within the Sac locus [28,29]. This gene is allelic in mice, and several reports identify a missense mutation (I60T) as being the most likely mutation accounting for the phenotypic differences [13,14,16,3033].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, in Drosophila, the behavioral and electrophysiological responses to trehalose are diminished in two mutants that carry deletions in the trehalose recognition gene, Gr5a [27]. In the mouse, variation in preference for sweet-tasting stimuli maps to the gene for T1R3, located within the Sac locus [28,29]. This gene is allelic in mice, and several reports identify a missense mutation (I60T) as being the most likely mutation accounting for the phenotypic differences [13,14,16,3033].…”
Section: Discussionmentioning
confidence: 99%
“…Tas1r2 and Tas1r3 overgo probes were radioactively labeled by the random hexa-nucleotide method, and hybridization and washing of membranes were as described [29]. We identified 47 positive BAC clones for cat Tas1r2 and cat Tas1r3, and sequenced all of the positive BAC ends.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using crosses between different inbred mouse strains have mapped the Sac locus to the subtelomeric region of mouse chromosome 4 and have shown that it affects sweetener preferences and the afferent responses of gustatory nerves to sweeteners . Our positional cloning study has shown that the Sac locus corresponds to the Tas1r3 gene and that Tas1r3 sequence variants are associated with sweetener preference phenotypes in genealogically diverse mouse strains . Additional evidence for identity of Sac and Tas1r3 was obtained in studies using congenic, transgenic and knockout mice .…”
Section: Within‐species Variation In Sweet Taste Preferencesmentioning
confidence: 65%
“…The discovery and identification of T1R as the receptors of sweet or umami stimuli were reviewed by Bachmanov and Beauchamp (2007) and Montmayeur and Matsunami (2002). Briefly, the mouse sac gene was found to encode a sweet taste receptor T1R3 (Bachmanov et al 1997(Bachmanov et al , 2001Li et al 2001Li et al , 2002a. Studies of functional expression in heterogeneous cells further showed that T1R3 combined with T1R2 can recognize all kinds of sweet substances including natural sugars, artificial sweeteners and d-amino acids (Li et al 2002a, b;Nelson et al 2001).…”
Section: Taste Receptorsmentioning
confidence: 99%